Strategies for Enzymatic Synthesis of Omega‐3 Structured Triacylglycerols from Camelina sativa Oil Enriched in EPA and DHA. Issue 5 (27th March 2019) - Castejón, Natalia; Señoráns, Francisco J.
Abstract : Enzymatic production of enriched eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) structured triacylglycerols (STAGs) is done in a two‐step reaction from a new source of omega‐3 α‐linolenic acid (ALA), Camelina sativa oil. A fast‐pressurized liquid extraction method with ethyl acetate as green solvent is used to produce camelina oil with a 39.3% yield in less than 20 min. In a first stage, camelina oil with a 29.7% of ALA is used to enzymatically produce 2‐monoacylglycerols (2‐MAGs) with high ALA composition in position sn ‐2 (49.8% of ALA) using Lipozyme TL IM at 25 °C. For omega‐3 incorporation into STAGs, several lipases are studied, with 2‐MAG and omega‐3 FAEEs at different ratios (1:5, 1:10, and 1:20 (w/w)), 10% (w/w) of biocatalyst at 35 °C. STAGs yields reached with EPA ethyl esters are notably higher than using DHA‐EE. Lipase from Candida antarctica B (CAL‐B) and Thermomyces lanuginosus (TLL) incorporate EPA into STAGs in the same degree, 95.1 and 95.5%, respectively. However, for enriched DHA STAGs, maximum reaction yield is reached with CAL‐B (81.0%). The transesterification method of 2‐MAGs from vegetable omega‐3 sources like camelina oil, with marine EPA and DHA FAEEs, opens new approaches for developing VLC‐PUFA fortified functional foods. Practical Applications : Results provided in this research not only demonstrate the efficiency of this enzymatic method for enriching camelina oil in EPA and DHA, but offer a very effective strategy for the development of omega‐3‐enriched products from other vegetable oil sources like chia or echium as ingredients for functional foods with recognized health claims for applications in nutraceutical and food industries. Camelina oil proved to be an excellent source to enzymatically produce 2‐MAGs enriched in omega‐3 ALA. Moreover, lipase screening with commercial biocatalysts establish the most appropriate strategy to reach maximum STAGs yields with direct application in industry. Tested lipases exhibit different degree of substrate specificity toward EPA and DHA, omega‐3 acids not present in natural seed oils. Thus, CAL‐B seems to be the most suitable lipase to produce high content EPA and DHA enriched STAGs from camelina oil as new food ingredients for nutraceutical applications. Enzymatic production of structured TAGs enriched in EPA and DHA is done in a two‐step reaction from a natural source of omega‐3 ALA, camelina oil, studying reaction kinetics and characterizing isolated products. Abstract : Enzymatic production of structured TAGs enriched in EPA and DHA is done in a two‐step reaction from a natural source of omega‐3 ALA, camelina oil, studying reaction kinetics and characterizing isolated products.